T-shirt (elections May 2004, president Gloria, September 21 Committee, Jun Lozada), bag (coll. Francia, M.). Sweatshirt (NDF)
T-shirt (elections May 2004, president Gloria, September 21 Committee, Jun Lozada), bag (coll. Francia, M.). Sweatshirt (NDF).